Pengaruh Tingkat Kesehatan Bank Dengan Menggunakan Pendekatan RBBR (Risk Based Bank Rating) dan Ukuran Bank Terhadap Pertumbuhan Laba Pada Bank Umum Konvensional Yang Terdaftar di BEI Periode 2018 – 2022 - Dewi Ariyani Rahman; Novita Weningtyas Respati; Sarwani, Sarwani (FKIP, Universitas Palangka Raya, 2025)
This research aims to explain the influence of bank health levels using the RBBR (Risk Based Bank Rating) approach and bank size on profit growth in Conventional Commercial Banks listed on the Indonesia Stock Exchange for the period 2018 - 2022. The RBBR approach includes Risk Profile, Good Carporate Governance, Earnings, and Capital and Bank Size. The method used in this research is a quantitative method that uses secondary data with documentation studies in the form of conventional commercial bank financial reports which have been published on the Indonesia Stock Exchange website, namely www.idx.co.id, Financial Services Authority http://www.ojk. go.id, Bank Indonesia www.bi.go.id, and websites of related banks. The population in this research is all Conventional Commercial Banks listed on the Indonesia Stock Exchange. The sampling technique in this research used purposive sampling, so that a sample of 39 banks was obtained. This research uses multiple linear regression analysis which is processed using the Statistical Package for Social Science (SPSS) 26. The results of this research show that Risk Profile which is proxied by Non Performing Loans (NPL) has a significant negative effect on profit growth, Earnings which is proxied by Return On Assets (ROA), and Capital which is proxied by Capital Adequacy Ratio (CAR) has a significant positive effect on growth. profit, while Good Corporate Govenrnance (GCG) and bank Size have no effect on profit growth. Practically, this research is to provide information, references and consideration for Conventional Commercial Banks listed on the Indonesia Stock Exchange to be able to increase bank profit growth by paying attention to the bank's health level and bank size by determining policies, making strategies and planning. to continue to improve the quality of bank performance, which will have an impact on increased profit growth, so that it can provide value for investors or other stakeholders